Recent advances in intestinal imaging - Sinha, Rakesh (Indian Journal of Radiology and Imaging, 2011)
In recent years, advances in scanner technology and competition from other specialties have produced rapid changes in the way the intestines are imaged. MRI and CT scan along with the traditional enteroclysis examination have emerged at the forefront of intestinal imaging. Functional modalities such as diffusion and perfusion imaging are also changing the way tumors and inflammatory bowel diseases are evaluated. CT colonography is now a valid alterative to optical colonoscopy. Contrast-enhanced USG is being used for the assessment of inflammation and post-treatment changes. In this review, recent advances in intestinal imaging are described.
Keywords: Computed tomography; intestines; magnetic resonance imaging